Immunogenicity and structures of a rationally designed prefusion MERS-CoV spike antigen - Pallesen, Jesper; Wang, Nianshuang; Corbett, Kizzmekia S.; Wrapp, Daniel; Kirchdoerfer, Robert N.; Turner, Hannah L.; Cottrell, Christopher A.; Becker, Michelle M.; Wang, Lingshu; Shi, Wei; Kong, Wing-Pui; Andres, Erica L.; et al. (Proceedings of the National Academy of Sciences - PNAS, 2017)
Middle East respiratory syndrome coronavirus (MERS-CoV) is a lineage C betacoronavirus that since its emergence in 2012 has caused outbreaks in human populations with case-fatality rates of ∼36%. As in other coronaviruses, the spike (S) glycoprotein of MERS-CoV mediates receptor recognition and membrane fusion and is the primary target of the humoral immune response during infection. Here we use structure-based design to develop a generalizable strategy for retaining coronavirus S proteins in the antigenically optimal prefusion conformation and demonstrate that our engineered immunogen is able to elicit high neutralizing antibody titers against MERS-CoV. We also determined high-resolution structures of the trimeric MERS-CoV S ectodomain in complex with G4, a stem-directed neutralizing antibody. The structures reveal that G4 recognizes a glycosylated loop that is variable among coronaviruses and they define four conformational states of the trimer wherein each receptor-binding domain is either tightly packed at the membrane-distal apex or rotated into a receptor-accessible conformation. Our studies suggest a potential mechanism for fusion initiation through sequential receptor-binding events and provide a foundation for the structure-based design of coronavirus vaccines.